Nutraceuticals and functional foods in human health and disease prevention - Preuss Harry G.; Bagchi Debasis (ed); Bagchi Debasis (ed) (Baco Raton CRC Press Taylor & Francis Group, 2019)
Obesity,Diabetes,and Metabolic Syndrome